BASF's carbon fibre PPA compounds offer an alternative to aluminium, magnesium. Issue 3 (March 2021) - Unknown
Abstract : BASF is expanding its Ultramid® Advanced polyphthalamide (PPA) portfolio with the addition of carbon fibre reinforced compounds with fillings of 20%, 30% and 40%. The company reports that these new materials make for extremely lightweight parts, can safely replace aluminium and magnesium without loss in stiffness and strength, and are electrically conductive.